The Dark Side of Emotion Recognition – Evidence From Cross-Cultural Research in Germany and China - Schmitt, Helena S.; Sindermann, Cornelia; Li, Mei; Ma, Yina; Kendrick, Keith M.; Becker, Benjamin; Montag, Christian (Frontiers in Psychology, 2020)
Background. The dark triad of personality (DT) comprises three antisocial personality traits (i.e., narcissism, Machiavellianism, and psychopathy) that are characterized by callousness and the motive to elevate the self while derogating other people. Previous research indicates that the positive relationship between the DT traits and interpersonally deviant behaviors is especially pronounced at high levels of emotional abilities. This has also been referred to as dark Emotional Intelligence (EI). Since prior studies predominantly examined dark EI via trait-approach, the present study targeted at providing evidence for dark EI using a behavioral measure of EI, namely the emotion recognition performance. In order to study the robustness and cross-cultural validity of findings, parallel investigations were conducted in Germany and China. Methods. A total of 198 German (Age: M=23.40, SD=5.88, 130 female) and 223 Chinese (Age: M=19.01, SD=1.06, 105 female) participants took part in an online survey and completed a set of questionnaires in German and Mandarin translations, respectively. DT traits were assessed by means of the Short Dark Triad Scale. As a behavioral measure of emotional abilities, participants completed the Eyes Test for emotional expressions of Caucasian and Asian models, respectively. Moreover, participants filled in the Emotional Manipulation Scale for the assessment of emotionally manipulative tactics. Results. Effects were highly gender- and culture-dependent. Among German females, Machiavellianism and narcissism showed the strongest positive associations with emotionally manipulative tactics at high levels of emotion recognition performance. A similar pattern of results was found among German males for psychopathy. None of the effects was observed in the Chinese female or male samples. Discussion. The present findings indicate that emotional abilities may constitute risk factors with the potential to promote rather than to prevent deviant behaviors especially in samples from Western cultures with pronounced scores on DT personality traits. Limitations and psychometric properties are discussed.